2015
DOI: 10.1073/pnas.1420687112
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing dynamics in large-scale functional connectivity predict perception

Abstract: Most brain activity occurs in an ongoing manner not directly locked to external events or stimuli. Regional ongoing activity fluctuates in unison with some brain regions but not others, and the degree of long-range coupling is called functional connectivity, often measured with correlation. Strength and spatial distributions of functional connectivity dynamically change in an ongoing manner over seconds to minutes, even when the external environment is held constant. Direct evidence for any behavioral relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
224
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(250 citation statements)
references
References 38 publications
23
224
2
1
Order By: Relevance
“…While the abovementioned studies show converging evidence for a beneficial role of a reduced DMN state before cognitive task onset, a number of other studies have recently shown a more variable role of the DMN for sensory tasks (Boly et al., 2007; Mayhew et al., 2013; Sadaghiani et al., 2009). These studies employed near‐threshold sensory tasks, on the one hand showing a lower prestimulus activation or connectivity predicted enhanced levels in detection performance (Boly et al., 2007), on the other hand showing a higher prestimulus DMN activation for more intense perception (e.g., more sensitive auditory stimulus detection, more extreme perception during thermal stimulation) of sensory stimuli (Mayhew et al., 2013; Sadaghiani et al., 2009, 2015). However, the tasks at hand relied primarily on processing in sensory areas, rather than higher‐order cognitive areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the abovementioned studies show converging evidence for a beneficial role of a reduced DMN state before cognitive task onset, a number of other studies have recently shown a more variable role of the DMN for sensory tasks (Boly et al., 2007; Mayhew et al., 2013; Sadaghiani et al., 2009). These studies employed near‐threshold sensory tasks, on the one hand showing a lower prestimulus activation or connectivity predicted enhanced levels in detection performance (Boly et al., 2007), on the other hand showing a higher prestimulus DMN activation for more intense perception (e.g., more sensitive auditory stimulus detection, more extreme perception during thermal stimulation) of sensory stimuli (Mayhew et al., 2013; Sadaghiani et al., 2009, 2015). However, the tasks at hand relied primarily on processing in sensory areas, rather than higher‐order cognitive areas.…”
Section: Discussionmentioning
confidence: 99%
“…The DMN might therefore play different roles with regard to task performance when integrating sensory and higher‐order cognitive processes. In contrast to sensory tasks, cognitive tasks such as the match‐to‐sample mental rotation task employed in the current study might increase the need to distribute connections across different modules instead of relying on network integrity (Sadaghiani et al., 2015). It might be possible that within diverse DMN states, the brain benefits from a less integrated DMN (manifested in less functional connectivity within the network) in order to respond optimally to a changing environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, evidence of functionally relevant network dynamics emerging over relatively “fast” timescales was provided by Sadaghiani et al (Sadaghiani, Poline, Kleinschmidt, & D’Esposito, 2015). This was enabled by trial-wise FC estimation over pre-stimulus windows in an auditory detection task.…”
Section: Capturing Functionally Relevant Network Dynamicsmentioning
confidence: 99%
“…6 Furthermore, the coordination of brain activity between disparate brain subnetworks is a dynamic and taskdependent process. [7][8][9][10] Temporal dynamic interactions within brain subnetworks play an important role in supporting brain information processing. 11,12 Fluctuations in brain systems involve a wide range of spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%